Skip-beat! 11 - Nakamura, Yoshiki (Shojo beat manga, 2008)
Ren, who is having trouble adjusting to his role as a love-struck suitor on the show "Tsukimori" decides to run away rather than admit his problems and Kyoko vows to find Ren and help him overcome his shyness.